Applied Regional Growth and Innovation Models - Kourtit, Karima; Nijkamp, Peter; Stimson, Robert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Modern spatial-economic systems exhibit a high degree of dynamics as a result of technological progress, demographic evolution or global change. In the past decade, an avalanche of new regional economic growth and innovation models has been put forward. This volume contains a unique collection of operational models of a strong applied nature that may be seen as original landmarks in the rich tradition of spatial-economic growth modelling. The contributors are recognized experts from different parts of the world.
Preface -- Part A: Knowledge and Innovation in Space -- Part B: Human Capital and Regional Growth -- Part C: Spatial Systems and Economic Development.
Keywords: Economics; Geography; Endogenous growth (Economics).; Regional economics; Economics/Management Science; Regional/Spatial Science; Economic Geography; Economic Growth; R & D/Technology Policy